NATURAL HISTORY OF LEIOCEPHALUS SEMILINEATUS IN ASSOCIATION WITH SYMPATRIC LEIOCEPHALUS SCHREIBERSII AND AMEIVA LINEOLATA - Nelson, Sonya E.; Banbury, Barb L.; Sosa, Roland A.; Powell, Robert; Parmerlee, John S. (Contemporary Herpetology, 2001)
We examined diet, habitat use, and behavior (focal animal observations of intraspecific interactions, escape behavior, and activity period) of Leiocephalus semilineatus from near Puerto Alejandro, Provincia de Barahona, República Dominicana, and compared some parameters to similar data collected at a site near Baní, Provincia de Peravia. Leiocephalus semilineatus is found in sympatry in dry scrub forests at both sites with Ameiva lineolata, an active-foraging teiid of approximately the same size, and at the Puerto Alejandro site with a larger congener, L. schreibersii. Leiocephalus semilineatus and L. schreibersii from Puerto Alejandro exhibited sexual size dimorphism, whereas L. semilineatus from the Baní site and A. lineolata did not. Leiocephalus semilineatus spent most of the time motionless; other observed activities were interactions with conspecifics, movement, and feeding. Lizards were active from shortly after sunrise to sundown, although activity peaked in late morning. Mean cloacal temperatures of L. semilineatus did not differ significantly from those of the other two species, but were significantly above ambient temperatures. Reproductive condition of collected specimens was examined and no correlation was found between snout-vent length and egg, follicle, or testis size. Clutch size was 1–2. Diets consisted primarily of invertebrates and did not differ significantly between the three species.